Interactions of imidazolium-based ionic liquids with oxide surfaces controlled by alkyl chain functionalization - Schernich, Stefan; Laurin, Mathias; Lykhach, Yaroslava; Tsud, Nataliya; Sobota, Marek; Skala, Tomas; Prince, Kevin C.; Taccardi, Nicola; Wagner, Valentin; Steinrück, Hans-Peter; Matolin, Vladimir; Wasserscheid, Peter; et al. (ChemPhysChem, 2013)
From a different angle: Thin films of functionalized ionic liquids are deposited on cerium oxides following a surface science approach. The functionalization of the alkyl chain changes its orientation with respect to the surface plane from normal to parallel. This then leads to a different surface chemistry at higher temperatures. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.